PENGEMBANGAN PRODUK ROWE LUWA MENGGUNAKAN METODE QUALITY FUNCTION DEPLOYMENT (QFD) - Ashri Indriati; Yusuf Andriana; Nur Kartika Indah Mayasti; Ade Chandra Iwansyah; Rohmah Luthfiyanti; Wawan Agustina; Ludia Simuruk Gasong (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
Financing risk is a condition of uncertainty that affects the success of a business to gain profit. Meanwhile, basic earning power is the ability to generate profits based on the capital owned. This study analyzes the risk and basic earning power of financing in the tapioca agro-industry using an interest-free calculation basis. The data used are primary data from field observations at the center of tapioca agro-industry in Ciluar, Bogor Regency, and secondary data from literature studies. The analysis is carried out by calculating the risk of loss and profitability of financing using the assumption of an acceptance rate of 10% of the total capital and when the level of acceptance falls -10% of the total capital owned. Furthermore, a comparison is made between tapioca agro-industries that use an interest-bearing financing scheme, including variables of risk of loss, income level, and profitability level. The research results prove that the bigger the loan used, the greater the risk to be borne. Another finding is that interest-free financing in the tapioca agro-industry has a higher return and income rate than interest-bearing financing.